Training on the Utilization of Coconut Husk Waste into High-Value and Environmentally Friendly Industrial and Agricultural Products (Coco Peat, Bistel, and Coco Bristle) - Nani Rohaeni; Abdur Rahman Irsyadi; Gema Ika Sari; Basrowi; Bambang Dwi Suseno; Azimi Faqqihuddin Arsyad; Muhammad Fahmi Baehaqi; Indriana Puspitasari (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This community empowerment program aimed to improve community knowledge, technical skills, and entrepreneurial interest in utilizing coconut coir waste to produce environmentally friendly and high-value products, namely coco peat, bistel (coco fiber), and coco bristle. The program addressed the issue of underutilized agricultural waste and the limited public awareness regarding its economic potential for supporting sustainable local economic development. Method: The program employed a participatory approach involving lectures, demonstrations, hands-on practice, interactive discussions, and technical assistance. The participants consisted of 17 community members and local small business actors. The effectiveness of the program was evaluated through observations and comparisons of participants’ knowledge and skill levels before and after the training activities. Practical Applications: The findings provide practical implications for community empowerment and sustainable waste management. The acquired skills can be applied in the development of small-scale businesses based on coconut coir processing, contributing to value-added product creation, income generation, and environmentally friendly agricultural and industrial practices. Conclusion: The program significantly improved participants’ knowledge and technical skills in processing coconut coir waste into valuable products. The findings indicate that coconut coir utilization can support community economic empowerment, reduce organic waste, and promote sustainable local resource-based industries.